Enterprise resource planning in healthcare system - V. I. Borshch; J. Sukhvitri (Ринкова економіка: сучасна теорія і практика управління)
Hospital information systems are usually heterogeneous and autonomous. However, to improve the efficiency of the hospital sector, it has been proposed that integrated management systems should be applied in the healthcare organizations. These integrated systems would help to improve hospitals’ processes and reduce operating.